Hydrodesulfurization catalyst and preparation method thereof
By using silicon-modified nickel-aluminum alloy support and molybdenum alkyl dithiophosphate and other active components in the hydrogenation catalyst, multiple Ni-Mo-S active sites are formed, which solves the problems of insufficient activity and coking carbon deposits in traditional catalysts when treating high aromatic hydrocarbons and high residual carbon raw materials, and achieves efficient hydrodesulfurization effect and deep hydrotreatment capacity.
Patent Information
- Application Number
- CN202311493957.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-10
- Publication Date
- 2025-05-13
- Estimated Expiration
- 2043-11-10
AI Technical Summary
When traditional hydrogenation catalysts treat low-quality raw materials with high aromatic hydrocarbons and high residual carbon content, they are insufficient in activity and are prone to coking carbon deposits. They are poor in activity when the metal content is high, and are not suitable for deep hydrotreatment.
Silicon-modified nickel-aluminum alloy is used as the support, combined with molybdenum alkyl dithiophosphate and/or molybdenum alkyl dithiocarbamate as active components, and the pore structure of the catalyst is optimized by vapor deposition method to form multiple Ni-Mo-S active points, thereby improving the utilization rate and catalytic activity of molybdenum.
The hydrodesulfurization capacity of the catalyst is significantly improved, especially when treating raw materials with high aromatic hydrocarbons and high residual carbon content, the occurrence of coking carbon deposits is avoided, and good activity is maintained when the metal content is high, which is suitable for deep hydrotreatment.
Smart Images

Figure BDA0004541974800000121 
Figure BDA0004541974800000131 
Figure BDA0004541974800000132
Abstract
Description
Technical Field
[0001] The invention relates to a hydrogenation catalyst, in particular to a hydrodesulfurization catalyst and a preparation method thereof. Background Art
[0002] Traditional alumina-nickel-molybdenum hydrogenation catalysts have limited hydrogenation metal nickel content, which limits the hydrogenation activity for processing raw materials with high aromatic content. In addition, traditional hydrogenation catalysts not only require high temperature and pressure, but are also prone to problems such as coking and carbon deposition.
[0003] CN103285914A discloses a method for preparing a hydrogenation pretreatment catalyst containing a silicon-aluminum-phosphorus-aluminum composite molecular sieve. The method comprises a silicon-aluminum-phosphorus-aluminum composite molecular sieve, a macroporous alumina and a modified alumina as a carrier, one or more of a VIB group metal and a VIII group metal as an active component, and P 2 O 5 As an additive, the catalyst exhibits excellent aromatic ring hydrogenation saturation performance and CN bond cracking ability during the hydrotreatment of inferior wax oil, thereby improving the catalyst's hydrodearomatization and hydrodenitrogenation performance. However, the strong acid carrier has a significant negative effect on the long-term stability of the catalyst.
[0004] CN111715232A discloses a supported hydrogenation catalyst and a preparation method thereof, wherein the salt of the active metal component is dissolved in water to obtain an impregnation solution, and the carrier is impregnated; the mixture obtained after the impregnation is subjected to a pressure treatment, wherein the pressure treatment is subjected to a pressure treatment of 0.2-20 MPa at a temperature of 110-300°C for 1-20 hours, and the obtained solid is the supported hydrogenation catalyst after drying and roasting. This method has excellent hydrodesulfurization performance even when the active metal content is extremely low, and the preparation method is simple to operate and has low production cost. However, when the metal content is high, the activity of this catalyst is poor, and it is not suitable for deep hydrogenation of oil products.
[0005] CN102302935A discloses a catalyst for oil product hydrogenation and dearomatization and a preparation method thereof. The catalyst is Al 2 O 3 -TiO 2 -ZnO composite oxide as a carrier, loaded with a certain amount of active components Ni or Cu. The catalyst can be used for solvent oil and gasoline hydrogenation dearomatization reaction, showing good low-temperature catalytic activity and resistance to sulfur and arsenic poisoning. However, this catalyst contains more small pores, and the hydrogenation effect on distillate oil with larger molecular weight is poor. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a hydrodesulfurization catalyst and a preparation method thereof. The hydrodesulfurization catalyst has a strong hydrodesulfurization ability for low-quality raw materials with high aromatics and high residual carbon content.
[0007] A first aspect of the present invention provides a hydrodesulfurization catalyst, which comprises a carrier and an active component, preferably a promoter, wherein the carrier comprises a silicon-modified nickel-aluminum alloy, the active component is organic molybdenum, preferably alkyl dithiophosphate molybdenum and / or alkyl dithiocarbamate molybdenum, and the promoter is organic zinc, preferably alkyl dithiophosphate zinc and / or alkyl dithiocarbamate zinc.
[0008] Further, the alkyl dithiophosphate molybdenum is selected from one or more of diisopropyl dithiophosphate molybdenum, dibutyl dithiophosphate molybdenum oxysulfide, and diisooctyl dithiophosphate molybdenum. The alkyl dithiocarbamate molybdenum is selected from one or more of dibutyl dithiocarbamate molybdenum and diisopropyl dithiocarbamate molybdenum.
[0009] Further, the alkyl zinc dithiophosphate is selected from one or more of dibutyl zinc dithiophosphate, isodecyl zinc dithiophosphate, diisooctyl zinc dithiophosphate, and di(tetradecyl) zinc dithiophosphate. The alkyl zinc dithiocarbamate is selected from one or more of diethyl zinc dithiocarbamate, ethylphenyl zinc dithiocarbamate, and dibutyl zinc dithiocarbamate.
[0010] Furthermore, in the present invention, the nickel-aluminum alloy has a wide selection range. The nickel-aluminum alloy has a conventional definition in the art, and its source is not particularly limited. It can be purchased commercially or made by itself, and any feasible method can be used to make it by itself.
[0011] Further, in the present invention, the amount of nickel and aluminum in the nickel-aluminum alloy is selected in a wide range. Preferably, based on the total amount of the nickel-aluminum alloy, the aluminum content is 50wt% to 95wt% and the nickel content is 5wt% to 50wt%. More preferably, based on the total amount of the nickel-aluminum alloy, the aluminum content is 70wt% to 90wt% and the nickel content is 10wt% to 30wt%. By adopting this preferred embodiment, not only can nickel and sulfur-containing organic molybdenum compounds be effectively combined to improve the hydrogenation performance of the catalyst, but the nickel content in the nickel-aluminum alloy is not too high.
[0012] Furthermore, the silicon-modified nickel-aluminum alloy is an organosilicon-modified nickel-aluminum alloy, and the organosilicon is specifically an alkoxysilane. Further preferably, the alkoxysilane is selected from at least one of methyltrimethoxysilane, triethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, butyltriethoxysilane and octyltriethoxysilane. Preferably, based on the total dry weight of the hydrodesulfurization catalyst, the hydrogenation catalyst is composed of SiO 2 The organosilicon compound content is 0.2% to 3%, preferably 0.5% to 2%. In this preferred embodiment, the modified nickel-aluminum alloy is used as the catalytic substrate in the catalyst to provide a large amount of activated hydrogen, which can provide conditions for hydrogen transfer, and organic molybdenum, especially dialkyl dithiophosphate molybdenum and / or alkyl dithiocarbamate molybdenum, is used as an active component. The sulfur-containing molybdenum species is combined with nickel to form more Ni-Mo-S active sites, providing hydrogenation centers, and further improving the utilization rate of molybdenum and the hydrogenation activity of the catalyst.
[0013] Furthermore, based on the total dry weight of the hydrogenation sulfur catalyst, the content of Al calculated as aluminum oxide is 62% to 84%, preferably 68% to 80%, the content of Ni calculated as nickel oxide is 8% to 18%, preferably 9% to 15%, the content of molybdenum calculated as molybdenum trioxide is 6% to 18%, preferably 8% to 17%, the content of silicon calculated as silicon dioxide is 0.2% to 3%, preferably 0.5% to 2%, and the content of the additive calculated as metal oxide is 1.5% to 7%, preferably 2% to 5.5%.
[0014] Furthermore, in the present invention, the dry basis measurement method of the hydrodesulfurization catalyst is as follows: in an air atmosphere, the catalyst is heated from 120°C at 3.0°C per minute to 420°C, then roasted for 4.0 hours, then heated at 3.0°C per minute and roasted at 550°C for 2.0 hours, and the obtained object is analyzed in a dry environment.
[0015] Furthermore, the content of each component in the dry basis can be analyzed by atomic emission spectrometry (ICP-AES). Specifically, the equipment is OPTIMA7000DV atomic emission spectrometer produced by PE. In a typical solution preparation process, 0.1 g of sample is dissolved in a solution with a volume ratio of 3 HCl:1 HNO 3 :0.5HF mixed solution, and then dilute the mixed solution with deionized water to a certain volume so that the content of the element to be measured in the solution is between 1-10ppm to increase the accuracy of the measurement data.
[0016] Furthermore, the analysis method of the metal organic compound in the catalyst can be used to analyze the product by XPS, and the test conditions of the XPS include: light source: Mg Kα, energy step: 0.05eV, scanning range: 200-250eV (molybdenum), 280-300eV (carbon). When analyzing the valence state of molybdenum, it is considered that the binding energy of the 3d5 / 2 orbit of molybdenum is 227-228eV for 0-valence molybdenum species, the binding energy of the 3d5 / 2 orbit of molybdenum is between 228-229eV for +2-valence molybdenum species, the binding energy of the 3d5 / 2 orbit of molybdenum is between 229-231eV for +4-valence molybdenum species, and the binding energy of the 3d5 / 2 orbit of molybdenum greater than 231eV for +5 or +6-valence molybdenum;
[0017] Among them, the 3d5 / 2 orbital of organic metal molybdenum is between 227-229eV, which belongs to the molybdenum species with valence between 0 and +2. The test method of other metal organic compounds, such as Ga, is similar to that of molybdenum. The analysis shows that the valence state of the above metal additives belongs to organic species with valence between 0 and +1, proving the existence of sulfur-containing organic molybdenum compounds.
[0018] Furthermore, in the catalyst provided by the present invention, when a metallic zinc organic compound is used, since the metallic zinc organic compound and the sulfur-containing organic molybdenum compound have similar physical and chemical properties, their distribution patterns on the surface of the nickel-aluminum alloy carrier are similar and their distribution positions are close, thus avoiding the phase separation of zinc and molybdenum, making the hydrogenation effect, especially the hydrodesulfurization effect, more obvious.
[0019] Furthermore, the present invention has a wide range of pore volume selection for the hydrodesulfurization catalyst. Preferably, the pore volume of the hydrodenitrogenation catalyst is 0.1 to 1 cm 3 / g, preferably 0.15 to 0.6 cm 3 / g.
[0020] Further, according to a preferred embodiment of the present invention, the average pore size of the hydrodesulfurization catalyst is 4 to 15 nm, preferably 6 to 12 nm.
[0021] Further, according to a preferred embodiment of the present invention, in the hydrodesulfurization catalyst, the pore volume of 0-3 nm pores accounts for 1%-10% of the total pore volume, preferably 2%-5%. The catalyst in the preferred embodiment is more conducive to mass transfer and diffusion of reactant molecules.
[0022] Further, according to some embodiments of the present invention, the pore volume of 0-3 nm pores and the total pore volume of the catalyst are determined by nitrogen isothermal adsorption-desorption method.
[0023] The second aspect of the present invention provides a method for preparing the above hydrodesulfurization catalyst, comprising:
[0024] An impregnation solution containing organic molybdenum and optional organic zinc is prepared and then impregnated onto a silicon-modified nickel-aluminum alloy carrier, and then dried to obtain a hydrodesulfurization catalyst.
[0025] Furthermore, the silicon-modified nickel-aluminum alloy carrier is an organosilicon-modified nickel-aluminum alloy carrier, and the method for modifying the nickel-aluminum alloy carrier with organosilicon includes: contacting the nickel-aluminum alloy with alkoxysilane gas for silicon modification. Preferably, the method also includes vacuum treatment of the nickel-aluminum alloy before the organosilicon modification and replacement treatment after the silicon modification. This method is more conducive to the deposition of alkoxysilane on the small pores of the nickel-aluminum alloy carrier.
[0026] Furthermore, the preferred preparation method of the hydrodesulfurization catalyst of the present invention comprises:
[0027] (a) vacuumizing the nickel-aluminum alloy carrier;
[0028] (b) introducing alkoxysilane gas into the carrier treated in step (a) to perform modification treatment;
[0029] (c) replacing the alkoxysilane gas described in step (b) with nitrogen and / or inert gas to obtain a modified nickel-aluminum alloy carrier;
[0030] (d) preparing an impregnation solution containing organic molybdenum and organic zinc, and then impregnating the solution onto the modified nickel-aluminum alloy carrier obtained in step (c), and drying the solution to obtain a hydrodesulfurization catalyst.
[0031] Furthermore, in step (a), the pore volume of the nickel-aluminum alloy carrier is 0.4 to 1.0 cm 3 / g, preferably with a pore volume of 0.5 to 0.9 cm 3 / g, the average pore diameter is 4-12nm, preferably 6-10nm, wherein the volume proportion of small pores smaller than 3.0nm is not higher than 20%, preferably 5-10%.
[0032] Furthermore, the present invention has a wide selection range for the particle size of the nickel-aluminum alloy carrier, and can be adaptively selected according to the actual application environment. Preferably, the average particle size of the nickel-aluminum alloy carrier is 1 to 8 mm, preferably 2 to 5 mm.
[0033] Furthermore, in step (a), the vacuum treatment conditions are: vacuum degree of 0.05-1.0 torr, preferably 0.1-0.5 torr, treatment time of 2-10 hours, preferably 4-8 hours, temperature of 50-140°C, preferably 60-120°C.
[0034] Furthermore, in step (b), before the alkoxysilane gas is introduced, the temperature is first raised according to the boiling point of the alkoxysilane used to make the alkoxysilane in a gaseous state. The alkoxysilane gas is preferably one or more of methyltrimethoxysilane, triethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, isobutyltriethoxysilane, and n-octyltriethoxysilane.
[0035] Furthermore, in step (b), at least one of nitrogen and / or an inert gas is introduced as a carrier gas while the alkoxysilane gas is introduced. The partial pressure of the alkoxyalkoxysilane gas is 0.02-1.0 MPa, preferably 0.05-0.5 MPa, the temperature of the modification treatment is 200-450°C, preferably 250-400°C, the time is 1.0-10.0 hours, preferably 2.0-8.0 hours, and the flow rate of the alkoxysilane gas is 1.0-20.0 mL / min·g -1 Nickel aluminum alloy carrier, preferably 3.0-15mL / min·g -1 Nickel aluminum alloy carrier.
[0036] Furthermore, in the present invention, the inert gas is preferably one of argon and neon or a mixed gas of several thereof.
[0037] Furthermore, in step (c), the replacement conditions include: the inert gas introduction rate is 0.5-5 mL / min·g -1 Nickel aluminum alloy carrier, preferably 1-4 mL / min·g -1 For the nickel-aluminum alloy carrier, the replacement time is 0.5-8.0 hours, preferably 1.0-4.0 hours, and the temperature is 100-400°C, preferably 150-350°C.
[0038] Furthermore, in step (d), an organic molybdenum source and an organic zinc source are mixed with a solvent to prepare an impregnation solution. The organic molybdenum source is one or more of alkyl dithiophosphate molybdenum and / or alkyl dithiocarbamate molybdenum. The organic zinc source is one or more of alkyl dithiophosphate zinc and / or alkyl dithiocarbamate molybdenum. The solvent is one or more of n-hexane, n-heptane, n-octane or n-nonane. In the impregnation solution, the concentrations of organic molybdenum and organic zinc are independently 0.1 to 3 mol / L.
[0039] Furthermore, in step (d), the impregnation may be performed by at least one of equal volume impregnation, supersaturated impregnation, etc. conventionally used in the art.
[0040] Furthermore, in step (d), the drying is vacuum drying, the vacuum degree is 0.5-5.0 torr, preferably 1.0-3.0 torr, the drying temperature is 60-150° C., preferably 70-120° C., and the drying time is 2.0-12.0 h, preferably 4.0-8.0 h.
[0041] Furthermore, the hydrodesulfurization catalyst needs to be activated before use. The treatment conditions include: hydrogen pressure of 0.1-1.0MPa, preferably 0.2-0.8MPa, treatment temperature of 80-250°C, preferably 120-200°C, treatment time of 0.5-5.0h, preferably 1.0-3.0h, hydrogen flow rate of 3.0-15.0mL / h·g -1 Hydrodesulfurization catalyst, preferably 5.0-10.0 mL / h·g -1 Hydrodesulfurization catalyst.
[0042] The third aspect of the present invention provides a use of the hydrodesulfurization catalyst in the hydrodesulfurization of secondary processed oil.
[0043] The application conditions include: reaction temperature 320-420°C, preferably 340-400°C, hydrogen pressure 4.0-20.0MPa, preferably 8.0-18.0MPa, hydrogen oil volume ratio 400:1-1500:1, preferably 600:1-1200:1, volume space velocity 0.2-2.0h -1 , preferably 0.3-1.2h -1 .
[0044] The properties of the secondary processing oil are as follows: the aromatic content is 30wt% to 80wt%, further 50wt% to 70wt%, and the sulfur content is 2000 to 15000μg·g -1 , nitrogen content is 500~3000μg·g -1 。
[0045] Compared with the prior art, the present invention has the following advantages:
[0046] 1. The hydrodesulfurization catalyst of the present invention uses alkyl dithiophosphate molybdenum (and / or alkyl dithiocarbamate molybdenum) as the molybdenum source. Due to the steric hindrance effect of alkyl substitution, the molybdenum sulfide species on the surface of the nickel-aluminum alloy is in a highly dispersed state. After mild hydrogen treatment, the Ni-Mo-S active phase obtained is compared with the molybdenum species obtained from the oxidized state after sulfidation and the non-supported MoS 2 Particles, this active phase has more active centers, which improves the utilization of molybdenum and the hydrogenation activity of the catalyst.
[0047] 2. The hydrodesulfurization catalyst of the present invention uses alkyl zinc dithiophosphate and / or alkyl zinc dithiocarbamate as an auxiliary agent. Since the alkyl zinc dithiophosphate and / or alkyl zinc dithiocarbamate have similar physical and chemical properties to the specific active component, their distribution patterns and distribution positions on the surface of the modified nickel-aluminum alloy carrier are similar, which avoids the phase separation of zinc and molybdenum and makes the effect of the auxiliary agent more obvious.
[0048] 3. The present invention adopts alkoxysilane-vapor deposition method to ensure that alkoxysilane is preferentially blocked in the small pores of the catalyst, thereby optimizing the pore structure of the nickel-aluminum alloy catalyst and preventing the subsequent deposition of molybdenum metal in the small pores. At the same time, the silicon on the surface of the nickel-aluminum alloy can effectively divide the nickel surface and prevent the aggregation of molybdenum species on the nickel surface. DETAILED DESCRIPTION
[0049] The present invention will be further described below in conjunction with the examples, but the following examples do not constitute a limitation of the present invention, wherein the percentages of the materials described are by mass percentage unless otherwise specified.
[0050] The properties of the nickel-aluminum alloy particles selected in the examples and comparative examples of the present invention are as follows: average particle size 4.1 mm, pore volume 0.72 cm 3 / g, the average pore size of the carrier is 8.3 nm, the volume of small pores less than 3 nm is 7.6%, the mass fraction of Al is 83.6%, and the mass fraction of Ni is 16.4%.
[0051] Example 1
[0052] 100.0 g of nickel-aluminum alloy particles were placed in a vacuum drying oven, the vacuum degree was controlled at 0.2 torr, the temperature was 80° C., and the treatment time was 4.0 hours.
[0053] The temperature of the vacuum drying oven was raised to 220° C., and nitrogen and methyltrimethoxysilane gas were introduced therein. The partial pressure of the methyltrimethoxysilane gas was 0.1 MPa, the gas flow rate was 400 mL / min, and the gas introduction time was 3.0 hours.
[0054] The temperature of the drying box was adjusted to 160° C., and the drying box was replaced with nitrogen at a rate of 200 mL / min. The replacement time was 1.0 hour, and the modified nickel-aluminum alloy carrier obtained was recorded as L-1.
[0055] Take 20.0 g of diisopropyl molybdenum dithiophosphate, 6.0 g of dibutyl zinc dithiophosphate, and 70.0 g of n-heptane to prepare an impregnation solution Q-1.
[0056] L-1 was impregnated with Q-1, and then vacuum dried at 70°C with a vacuum degree of 1.0 torr for 4 hours. The obtained catalyst was designated Cat-1.
[0057] Example 2
[0058] 100.0 g of nickel-aluminum alloy particles were placed in a vacuum drying oven, the vacuum degree was controlled at 0.4 torr, the temperature was 100° C., and the treatment time was 5.0 hours.
[0059] The temperature of the vacuum drying oven was raised to 240° C., and nitrogen and triethoxysilane were introduced therein. The gas partial pressure of triethoxysilane was 0.1 MPa, the gas flow rate was 450 mL / min, and the gas introduction time was 4.0 hours.
[0060] The temperature of the drying box was adjusted to 170° C., and the drying box was replaced with nitrogen at a rate of 200 mL / min. The replacement time was 1.5 hours, and the modified nickel-aluminum alloy carrier was obtained and recorded as L-2.
[0061] Take 25.0 g of dibutyl dithiophosphorothioate molybdenum oxide sulfide, 8.0 g of diisooctyl zinc dithiophosphate, and 70.0 g of n-octane to prepare the impregnation solution Q-2.
[0062] L-2 was impregnated with Q-2, and then vacuum dried at 90°C with the vacuum degree controlled at 1.0 torr for 4 hours. The obtained catalyst was designated as Cat-2.
[0063] Example 3
[0064] 100.0 g of nickel-aluminum alloy particles were placed in a vacuum drying oven, the vacuum degree was controlled at 0.5 torr, the temperature was 120° C., and the treatment time was 5.0 hours.
[0065] The temperature of the vacuum drying oven was raised to 270° C., and nitrogen and isobutyltriethoxysilane were introduced therein. The gas partial pressure of isobutyltriethoxysilane was 0.1 MPa, the gas flow rate was 500 mL / min, and the gas introduction time was 5.0 hours.
[0066] The temperature of the drying box was adjusted to 200° C., and the drying box was replaced with nitrogen at a rate of 200 mL / min. The replacement time was 2.0 hours, and the modified nickel-aluminum alloy carrier obtained was recorded as L-3.
[0067] 20.0 g of molybdenum diisopropyldithiocarbamate, 4.0 g of zinc diethyldithiocarbamate, and 70.0 g of n-nonane were used to prepare an impregnation solution Q-3.
[0068] L-3 was impregnated with Q-3, and then vacuum dried at 120°C with the vacuum degree controlled at 1.0 torr for 4 hours. The obtained catalyst was designated as Cat-3.
[0069] Example 4
[0070] 100.0 g of nickel-aluminum alloy particles were placed in a vacuum drying oven, the vacuum degree was controlled at 0.5 torr, the temperature was 120° C., and the treatment time was 5.0 hours.
[0071] The temperature of the vacuum drying oven was raised to 380° C., and nitrogen and n-octyltriethoxysilane were introduced therein. The gas partial pressure of n-octyltriethoxysilane was 0.1 MPa, the gas flow rate was 600 mL / min, and the gas introduction time was 5.0 hours.
[0072] The temperature of the drying box was adjusted to 200° C., and the drying box was replaced with nitrogen at a rate of 200 mL / min. The replacement time was 2.0 hours, and the obtained modified nickel-aluminum alloy carrier was recorded as L-4.
[0073] 25.0 g of molybdenum dibutyl dithiocarbamate, 6.0 g of zinc dibutyl dithiocarbamate, and 70.0 g of n-decane were used to prepare an impregnation solution Q-4.
[0074] L-4 was impregnated with Q-4, and then vacuum dried at 120°C with the vacuum degree controlled at 1.0 torr for 4.0 hours. The obtained catalyst was designated as Cat-4.
[0075] Comparative Example 1
[0076] 100.0 g of nickel-aluminum alloy particles were placed in a vacuum drying oven, the vacuum degree was controlled at 0.5 torr, the temperature was 120° C., and the treatment time was 5.0 hours. The obtained nickel-aluminum alloy carrier was recorded as DL-1.
[0077] 20.0 g of molybdenum diisopropyldithiocarbamate, 4.0 g of zinc diethyldithiocarbamate, and 75.0 g of n-octane were used to prepare an impregnation solution DQ-1.
[0078] DL-1 was impregnated with DQ-1 and then vacuum dried at 120°C with the vacuum degree controlled at 1.0 torr for 4 hours. The obtained catalyst was recorded as DCT-1.
[0079] Comparative Example 2
[0080] The preparation method of the modified nickel-aluminum alloy carrier L-3 is the same as that in Example 3.
[0081] 20.0 g of carbonyl molybdenum, 7.0 g of zinc octoate, and 70.0 g of toluene were prepared into solution DQ-2.
[0082] L-3 was impregnated with DQ-2, and then vacuum dried at 120°C, with the vacuum degree controlled at 1.0 torr and the drying time being 4.0 hours to obtain an oxidized catalyst.
[0083] Weigh 20.0 g of the above-mentioned oxidized catalyst, put it into a tubular reactor, and carry out conventional sulfidation treatment. The treatment conditions are: the sulfiding liquid is a cyclohexane solution containing 5.0% dimethyl disulfide by mass, the amount of sulfiding liquid is 40.0 g / h, the hydrogen pressure is 4.0 MPa, the hydrogen flow rate is 200 mL / min, the sulfidation temperature is 340° C., and the sulfidation time is 6.0 hours. The obtained catalyst is recorded as DCT-2.
[0084] Comparative Example 3
[0085] The preparation method of the modified nickel-aluminum alloy carrier L-3 is the same as that in Example 3.
[0086] 12.0 g of molybdenum disulfide powder and 2.0 g of zinc sulfide powder were dissolved in a mixed solution of 40.0 g of n-octane and 30.0 g of DMDS to prepare an impregnation solution named DQ-3.
[0087] L-3 was impregnated with DQ-3 and then vacuum dried at 120°C with the vacuum degree controlled at 1.0 torr for 4 hours. The obtained catalyst was recorded as DCT-3.
[0088] Catalyst activation
[0089] 20.0 g of catalysts Cat-1, Cat-2, Cat-3, Cat-4, DCT-1, DCT-2, and DCT-3 were weighed respectively and placed in a tubular reactor. The activation conditions were: temperature 120°C, hydrogen pressure 0.5 MPa, hydrogen flow rate 150.0 mL / min, and activation time 2.0 hours.
[0090] Embodiment 5-8
[0091] The effects of the activated catalysts Cat-1, Cat-2, Cat-3 and Cat-4 in each example were evaluated respectively, and the properties of the feedstock oil are shown in Table 2.
[0092] 20.0 g of each activated catalyst was loaded into a fixed bed reactor to conduct a catalyst hydrogenation evaluation experiment under the following conditions:
[0093] The reaction temperature is 360℃, the hydrogen pressure is 11.0MPa, the hydrogen-oil ratio is 1000:1, and the volume space velocity is 0.8h -1 After 1000 hours of reaction, the sample analysis results are shown in Table 3.
[0094] Comparative Examples 4-6
[0095] 20.0 g of the activated catalysts of Comparative Examples 1-3 were respectively taken and loaded into a fixed bed reactor to carry out a hydrogenation evaluation experiment of the catalysts. The feedstock oil and reaction conditions were the same as those of Example 5.
[0096] Table 1 Catalyst composition and properties
[0097]
[0098]
[0099] Table 2 Raw oil properties
[0100]
[0101] Table 3 Catalyst evaluation results
[0102]
[0103]
[0104] It can be seen from the evaluation results that the use of the hydrodesulfurization catalyst of the present invention has a good hydrorefining effect and aromatic saturation effect on the treatment of heavy secondary processed oil products.
Claims
1. A hydrodesulfurization catalyst, characterized in that: The hydrodesulfurization catalyst comprises a carrier and an active component, preferably an auxiliary agent, wherein the carrier comprises a silicon-modified nickel-aluminum alloy, the active component is organic molybdenum, preferably alkyl dithiophosphate molybdenum and / or alkyl dithiocarbamate molybdenum, and the auxiliary agent is organic zinc, preferably alkyl dithiophosphate zinc and / or alkyl dithiocarbamate zinc.
2. The hydrodesulfurization catalyst according to claim 1, characterized in that The alkyl dithiophosphate molybdenum is selected from one or more of diisopropyl dithiophosphate molybdenum, dibutyl dithiophosphate molybdenum oxysulfide, and diisooctyl dithiophosphate molybdenum; the alkyl dithiocarbamate molybdenum is selected from one or more of dibutyl dithiocarbamate molybdenum and diisopropyl dithiocarbamate molybdenum.
3. The hydrodesulfurization catalyst according to claim 1, characterized in that The alkyl zinc dithiophosphate is selected from one or more of dibutyl zinc dithiophosphate, isodecyl zinc dithiophosphate, diisooctyl zinc dithiophosphate, and di(tetradecyl) zinc dithiophosphate; the alkyl zinc dithiocarbamate is selected from one or more of diethyl zinc dithiocarbamate, ethylphenyl zinc dithiocarbamate, and dibutyl zinc dithiocarbamate.
4. The hydrodesulfurization catalyst according to claim 1, characterized in that The silicon-modified nickel-aluminum alloy is an organosilicon-modified nickel-aluminum alloy, and the organosilicon is specifically an alkoxysilane; preferably, the alkoxysilane is selected from at least one of methyltrimethoxysilane, triethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, butyltriethoxysilane and octyltriethoxysilane.
5. The hydrodesulfurization catalyst according to claim 1, characterized in that Based on the total dry weight of the hydrogenation sulfur catalyst, the content of Al calculated as aluminum oxide is 62% to 84%, preferably 68% to 80%, the content of Ni calculated as nickel oxide is 8% to 18%, preferably 9% to 15%, the content of molybdenum calculated as molybdenum trioxide is 6% to 18%, preferably 8% to 17%, the content of silicon calculated as silicon dioxide is 0.2% to 3%, preferably 0.5% to 2%, and the content of the additive calculated as metal oxide is 1.5% to 7%, preferably 2% to 5.5%.
6. The hydrodesulfurization catalyst according to claim 1, characterized in that The properties of the hydrodesulfurization catalyst include: a pore volume of 0.1 to 1 cm 3 / g, preferably 0.15 to 0.6 cm 3 / g; the average pore diameter is 4 to 15 nm, preferably 6 to 12 nm; the pore volume of 0 to 3 nm pores accounts for 1% to 10% of the total pore volume, preferably 2% to 5%.
7. The method for preparing a hydrodesulfurization catalyst according to any one of claims 1 to 6, characterized in that: include: An impregnation solution containing organic molybdenum and optional organic zinc is prepared and then impregnated onto a silicon-modified nickel-aluminum alloy carrier, and then dried to obtain a hydrodesulfurization catalyst.
8. The method according to claim 7, characterized in that The silicon-modified nickel-aluminum alloy carrier is an organosilicon-modified nickel-aluminum alloy carrier, and the method for modifying the nickel-aluminum alloy carrier with organosilicon includes: contacting the nickel-aluminum alloy with alkoxysilane gas for silicon modification; preferably, the method also includes vacuum treatment of the nickel-aluminum alloy before the organosilicon modification and replacement treatment after the silicon modification.
9. The method according to claim 7 or 8, characterized in that: The preparation method of the hydrodesulfurization catalyst comprises: (a) vacuumizing the nickel-aluminum alloy carrier; (b) introducing alkoxysilane gas into the carrier treated in step (a) to perform modification treatment; (c) replacing the alkoxysilane gas described in step (b) with nitrogen and / or inert gas to obtain a modified nickel-aluminum alloy carrier; (d) preparing an impregnation solution containing organic molybdenum and organic zinc, and then impregnating the solution onto the modified nickel-aluminum alloy carrier obtained in step (c), and drying the solution to obtain a hydrodesulfurization catalyst.
10. The method according to claim 9, characterized in that In step (a), based on the total amount of the nickel-aluminum alloy, the content of aluminum as the element is 50wt% to 95wt%, and the content of nickel as the element is 5wt% to 50wt%; preferably, based on the total amount of the nickel-aluminum alloy, the content of aluminum as the element is 70wt% to 90wt%, and the content of nickel as the element is 10wt% to 30wt%.
11. The method according to claim 9, characterized in that In step (a), the vacuum treatment conditions are: vacuum degree of 0.05-1.0 torr, preferably 0.1-0.5 torr, treatment time of 2-10 hours, preferably 4-8 hours, temperature of 50-140°C, preferably 60-120°C.
12. The method according to claim 9, characterized in that In step (b), the alkoxysilane gas is selected from one or more of methyltrimethoxysilane, triethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, isobutyltriethoxysilane and n-octyltriethoxysilane.
13. The method according to claim 9, characterized in that In step (b), at least one of nitrogen and / or an inert gas is introduced as a carrier gas while the alkoxysilane gas is introduced; the partial pressure of the alkoxysilane gas is 0.02-1.0 MPa, preferably 0.05-0.5 MPa, the temperature of the modification treatment is 200-450° C., preferably 250-400° C., the time is 1.0-10.0 hours, preferably 2.0-8.0 hours, and the flow rate of the alkoxysilane gas is 1.0-20.0 mL / min·g -1 Nickel aluminum alloy carrier, preferably 3.0-15mL / min·g -1 Nickel aluminum alloy carrier.
14. The method according to claim 9, characterized in that In step (c), the replacement conditions include: the inert gas introduction rate is 0.5-5mL / min·g -1 Nickel aluminum alloy carrier, preferably 1-4 mL / min·g -1 For the nickel-aluminum alloy carrier, the replacement time is 0.5-8.0 hours, preferably 1.0-4.0 hours, and the temperature is 100-400°C, preferably 150-350°C.
15. The method according to claim 9, characterized in that In step (d), the organic molybdenum source and the organic zinc source are mixed with a solvent to prepare an impregnation solution; the solvent is one or a mixture of n-hexane, n-heptane, n-octane or n-nonane; in the impregnation solution, the concentrations of the organic molybdenum and organic zinc are independently 0.1 to 3 mol / L.
16. The method according to claim 9, characterized in that In step (d), the drying is vacuum drying, the vacuum degree is 0.5-5.0 torr, preferably 1.0-3.0 torr, the drying temperature is 60-150° C., preferably 70-120° C., and the drying time is 2.0-12.0 h, preferably 4.0-8.0 h.
17. Use of the hydrodesulfurization catalyst according to any one of claims 1 to 6 or the hydrodesulfurization catalyst prepared according to any one of claims 7 to 16 in the hydrodesulfurization of secondary processed oil.
Citation Information
Patent Citations
Catalyst for oil product hydrodearomatization and preparation method thereof
CN102302935A
Preparation method for hydrogenation pretreatment catalyst containing silicon aluminum-phosphorus aluminum composite molecule sieve
CN103285914A
Supported hydrogenation catalyst as well as preparation method and application thereof
CN111715232A
Hydrodesulfurization catalyst as well as preparation method and application thereof
CN114425449A
Hydroprocessing catalyst and method of making the same
US20110000824A1